Land use change and soil carbon pools: Evidence from a long-term silvopastoral - Fornara, Dario A.; Olave, Rodrigo; Burgess, Paul J.; Delmer, Aude; Upson, Matthew; McAdam, Jim (Springer, 2017)
Multi-functional silvopastoral systems provide a wide range of services to human society including the regulation of nutrients and water in soils and the sequestration of atmospheric carbon dioxide (CO2). Although silvopastoral systems significantly contribute to enhance aboveground carbon (C) sequestration (e.g. C accumulation in woody plant biomass), their long-term effects on soil C pools are less clear. In this study we performed soil physical fractionation analyses to quantify the C pool of different aggregate fractions across three land use types including (1) silvopastoral system with ash trees (Fraxinus excelsior L.), (2) planted woodland with ash trees, and (3) permanent grassland, which were established in 1989 at Loughgall, Northern Ireland, UK. Our results show that 26 years after the conversion of permanent grassland to either silvopastoral or woodland systems, soil C (and N) stocks (0–20 cm depth) did not significantly change between the three land use types. We found, however, that permanent grassland soils were associated with significantly higher C pools (g C kg−1 soil; P < 0.03) of the large macro-aggregate fraction (> 2 mm) whereas soil C pools of the micro-aggregate (53–250 μm) and silt and clay (< 53 μm) fractions were significantly higher in the silvopastoral and woodland systems (P < 0.05). A key finding of this study is that while tree planting on permanent grassland may not contribute to greater soil C stocks it may, in the long-term, increase the C pool of more stable (recalcitrant) soil micro-aggregate and silt and clay fractions, which could be more resilient to environmental change.
Keywords: Agroforestry; Carbon sequestration; Ecosystem services; Soil aggregates; Soil physical fractionation; Soil nitrogen